Самовиховання особистості дитини у психолого-педагогічній спадщині Г. А. Лінднера - Клим, Мар’яна (Studies in Comparative Education, 2014)
Статтю присвячено аналiзу особливостей процесу самовиховання особистості дитини у науковій спадщині Г. А. Лінднера. Встановлено, що у працях дослідника відбулася комплексна переоцінка сфери виховання та самовиховання дитини. Особливу увагу приділено необхідності розуміння дитинства, яке синхронно пов’язане з простором дорослих. У дослідженні встановлено, що самовиховання особистості дитини у науковій спадщині Г. А. Лінднера визначається як цілеспрямоване, активне входження в оточуючий соціум, яке потребує певних педагогічних умов – гуманізації процесу становлення особистості, відповідності змісту, обсягу і характеру педагогічної діяльності можливостям та умовам розвитку суспільства. Визначено, що у творчій спадщині науковця дитина посідає особливе місце. Самовиховання дитини вважається пріоритетним напрямом дошкільної освіти, сфери сімейного виховання та соціального виховання і водночас важливим системним педагогічно виваженим процесом. Статья посвящена анализу особенностей процеса самовоспитания личности ребенка в научном наследии Г. А. Линднера. Доказано, что в его трудах состоялась комплексная переоценка сферы воспитания и самовоспитания ребенка. Особое внимание уделяется необходимости понимания детства, которое синхронно связано с пространством взрослых. В исследовании установлено, что самовоспитание личности ребенка в научном наследии Г. А. Линднера определяется как целенаправленное, активное вхождение в окружающий социум, которое требует определенных педагогических условий – гуманизации процесса становления личности, соответствия содержания, объема и характера педагогической деятельности возможностям и условиям данного социума. Определено, что в творческом наследии ученого ребенок занимает особое место. Самовоспитания ребенка считалось приоритетным направлением дошкольного образования, сферы семейного воспитания и социального воспитания и одновременно важным системным педагогически взвешенным процессом. The article is devoted to the analysis of the process of child’s self-identity in the scientific heritage of G. A. Lindner. The comprehensive reassessment of the scope of education and self-education of the child has been made in his writings. Particular attention is paid to the need for understanding of childhood, which is simultaneously connected with space adults. The self-identity of the child in the G. Lindner scientific heritage is defined as purposeful, active entry in the surrounding society, which required certain pedagogical conditions – humanizing the process of identity formation, matching the content, scope and nature of educational activities opportunities and conditions of the society. It was determined that in the artistic heritage of scholar child took part a special place. Child self-education was considered a priority in pre-school education, family, social education and an important pedagogically systemic process. Pedagogue advised to integrate knowledge from educational anthropology, educational psychology, theology and teaching methodology in the process of self-identity. During this time G. A. Lindner was trying to develop their own vision of a dynamic concept of J. Herbart. The idea of self-identity, which includes the character’s variability of education depends on the mental state of a particular social group, social relations and the status of the individual within the team are presented in his works.